Min-max optimal control of linear systems with uncertainty and terminal state constraints - Wu, C.; Teo, Kok Lay; Wu, S. (Pergamon, 2013)
In this paper, a class of min–max optimal control problems with continuous dynamical systems and quadratic terminal constraints is studied. The main contribution is that the original terminal state constraint in which the disturbance is involved is transformed into an equivalent linear matrix inequality without disturbance under certain conditions. Then, the original min–max optimal control problem is solved via solving a sequence of semi-definite programming problems. An example is presented to illustrate the proposed method.